Sensory evaluation and study of the shelf life of aromatic tea made from plantain (Plantago Major L.), Cinnamon (Cinnamomum Verum) and Subtle Lemon (Citrus Aurantifolia Swingle) - Talavera Sardón, Martin Alonso (2019)
The research work was aimed evaluate the sensory characteristics and shelf life of aromatic tea made from plantain (Plantago major L), cinnamon (Cinnamomum verum) and subtle lemon (Citrus aurantifolia swingle). To obtain the results, physicochemical parameters such as humidity and ash were evaluated. Microbiological analyzes were also carried out, such as: Mesophilic Aerobics and Total Coliforms; for the sensory evaluation, the consumers evaluated six treatments of different concentrations, where it was evaluated: Odor, taste, color and general appearance applied to thirty judges. The results showed that in the physicochemical analysis with regard to humidity, it had an average of 87% in plantain, 85% in lemon and 5.35% in cinnamon, ash with 1.79% in plantain, 0.46% in lemon and 4.25% in cinnamon, with respect to the microbiological analysis of the samples, the plantain had a higher level of contamination a total of 7.1 x 104 CFU / g in microbiological analysis of aerobic mesophiles being significant with a 95% probability, besides predominance in total coliforms with 1.27 x 104 CFU / g. The sensory evaluation gave the best sensory average with 3.83 points interpreted as a good product corresponding to the T1 treatment, with the odor and taste being the most relevant with 3.87 points. Analysis of variance shows significant differences between their averages at 95% probability in terms of sensory evaluation; the final characteristics of the aromatic tea based on plantain, cinnamon and lemon were 10.033% humidity and 1.21% ash. For the study of the useful life of the food, the method of mathematical prediction of Arrhenius was used, for which a shelf life of 8.95 months was obtained, subjected to a temperature of 25 ºC, this result is superior to the other tests subjected to 35 ° C and 45 ° C with a shelf life of 6.92 and 5.43 months respectively, according to the analysis of variance (ANOVA) these results do not show a statistically significant relationship (p = 0.0524) between the useful life and the temperature, with a confidence level of 95%.